Receptive vocabulary acquisition through 'Storybird' - Shukri, Athirah (Penerbit UTM Press, 2017)
Knowledge of vocabulary is important for a learner of a language to be able to perform in all the four skills of reading, listening, writing and speaking in the target language. Despite its importance, language teaching or training generally puts lesser emphasis on its importance or the teaching of vocabulary still adopts a traditional teaching approach. With the advancement in computer technology and the emerging development of tools and software, vocabulary learning has moved beyond classical reading method. This present study explores the effects of online reading through the use of ‘Storybird’ tool on ESL learners’ receptive vocabulary. It aims to ascertain if reading on ‘Storybird’ as a tool within a classroom context could improve learners’ receptive vocabulary. The data was collected through the procedure of pre-test, treatment and post-test without control group. The result of the paired sample t-test show significant gains in the 3000-word level vocabulary test.